Manual of IIUM land use and landscape character survey tool (i-LULACAST) - Abdullah, Alias; Hj. Mohd. Noor, Norzailawati; Zakariya, Khalilah; Ibrahim, Illyani; Nizarudin, Norhanis Diyana; N Murtaza, Fatin Farhana; Ab Rahman, Saifol Anwar (2021)
The step-by-step manual and guide of the IIUM Land Use and Landscape Character Survey Tool (i-LULACAST) to the users for data collection and to the administrator for monitoring and analyzing the data for Kajian Meningkatkan Imej Serta Identiti Bandar Diraja Pekan, Pahang